Histological features used in the diagnosis of melanoma are frequently found in benign melanocytic naevi. Issue 4 (24th March 2005) - Urso, C; Rongioletti, F; Innocenzi, D; Batolo, D; Chimenti, S; Fanti, P L; Filotico, R; Gianotti, R; Lentini, M; Tomasini, C; Pippione, M
Abstract : Aims: The histological features used in the diagnosis of melanoma may be present in benign naevi, but quantitative data are not available. The aim of this study was to establish the real prevalence of such features in naevi. Methods: Ten dermatopathologists, from nine Italian institutions, studied a series of naevi. Eleven histological parameters currently used in melanoma diagnosis were analysed: asymmetry, poor circumscription, predominance of single melanocytes, irregular confluent nests, suprabasal melanocytes, hair follicle involvement, absence of maturation, cytological atypia, dermal lymphocytic infiltrate, mitoses, and necrosis. Results: Ninety one naevi were examined: 22 junctional, 59 compound, and 10 intradermal. None of the studied parameters was seen in 22 of the benign naevi studied. One or more investigated features were found in 69 naevi. Poor circumscription was found in 49 cases, single melanocytic predominating in 42, asymmetry in 41, irregular confluent nests in 16, cytological atypia in 14, suprabasal melanocytes in seven, and hair follicle involvement in seven; absence of maturation, mitoses and necrosis were not found. Conclusions: The histological features used for the histological diagnosis of melanoma are often present in benign melanocytic naevi. This suggests a critical, non-mechanical use of them in melanoma diagnosis.